Wyoming - Hanson-Harding, Alexandra (New York Children's Press, 2003)
An introduction to the state of Wyoming, describing its geography, history, government, people, economy, and more
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: Wyoming -- Juvenile literature; Wyoming